The low-lying quartet electronic states of group 14 diatomic borides XB (X = C, Si, Ge, Sn, Pb). (April 2018) - Pontes, Marcelo A. P.; de Oliveira, Marcos H.; Fernandes, Gabriel F. S.; Da Motta Neto, Joaquim D.; Ferrão, Luiz F. A.; Machado, Francisco B. C.
Highlights: Transition probabilities and radiative lifetime. Molecular constants and spin-orbit effects. Possible spectroscopic detection of the (1) 4 Π→ X 4 Σ − band transition for all species. The (2) 4 Σ − state is predissociative in GeB and repulsive in SnB and PbB. Abstract: The present work focuses in the characterization of the low-lying quartet electronic and spin-orbit states of diatomic borides XB, in which X is an element of group 14 (C, Si, Ge, Sn, PB). The wavefunction was obtained at the CASSCF/MRCI level with a quintuple-ζ quality basis set. Scalar relativistic effects were also taken into account. A systematic and comparative analysis of the spectroscopic properties for the title molecular series was carried out, showing that the (1) 4 Π→ X 4 Σ − transition band is expected to be measurable by emission spectroscopy to the GeB, SnB and PbB molecules, as already observed for the lighter CB and SiB species. Graphical abstract: